Digital Da'wah, SIMKAH, and Religious Bureaucracy in Indonesian Islamic Marriage Governance - Citra Sari; Elce Purwandari; Depi Putri (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2026)
The digital transformation of Islamic public services has significantly reshaped marriage administration practices within the Offices of Religious Affairs (KUA) in Indonesia. This study aims to analyze the implementation of the Marriage Management Information System (SIMKAH) at KUA Gandus, Palembang, and examine its role as a form of administrative da‘wah and digital Islamic governance. This research employed a qualitative case study approach using semi-structured interviews, documentation, and thematic analysis. The participants consisted of penghulu, SIMKAH operators, administrative staff, Islamic religious counselors, and prospective brides and grooms involved in SIMKAH-based marriage services. The findings reveal that SIMKAH has transformed conventional marriage administration into a more efficient, transparent, and digitally integrated public service system. The implementation of SIMKAH improves administrative accuracy, accelerates registration procedures, strengthens legal marriage awareness, and expands public accessibility to Islamic marriage services. The study further demonstrates that SIMKAH functions not merely as a technological administrative instrument but also as a medium of administrative da‘wah through digital legal education and institutional guidance. However, several challenges remain, including digital inequality, limited technological literacy, and unstable internet infrastructure. The novelty of this study lies in introducing the concept of administrative da‘wah within digital Islamic public services, where Islamic bureaucracy simultaneously functions as a mechanism of governance, religious education, and social transformation.